Use of Red Cactus Pear (Opuntia ficus-indica) Encapsulated Powder to Pigment Extruded Cereal - Ruiz Gutiérrez, Martha Graciela; Amaya Guerra, Carlos Abel; Quintero Ramos, Armando; Pérez Carrillo, Esther; Meléndez Pizarro, Carmen O. (Wiley, 2017)
Encapsulated powder of the red cactus pear is a potential natural dye for the food industry and a known antioxidant. Although the use of this powder is possible, it is not clear how it alters food properties, thus ensuing commercial acceptability. The aim of thisstudywastoevaluatetheeffectofencapsulatedpowderoftheredcactuspearonthephysicochemicalpropertiesofextruded cereals. The powder was mixed (2.5, 5.0, and 7.5% w/w) with maize grits and extruded (mix moisture 22%, temperature 100∘C, and screw speed 325rpm). The physical, chemical, and sensory characteristics of the extruded cereal were evaluated; extruded cerealwithoutencapsulatedpowderwasusedasacontrol.Allcerealextrudatespigmentedwiththeencapsulatedpowdershowed statisticallysignificantdifferences(